Diagnostic dilemma in cheek lesions in the paediatric age group: thinking beyond the expected - Joshi, Anagha R.; Sankhe, Ashwini; Patankar, Soniya H.; Rahatgaonkar, Mrinalini M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Rhabdomyosarcoma (RMS), a tumour of skeletal muscle origin, is the most common soft tissue sarcoma encountered in childhood. The head and neck region is the most common site of occurrence of RMS. RMS is a highly malignant tumour with extensive local invasions and early haemorrhagic and lymphatic dissemination. Despite the advances in treatment modalities, with aggressive approaches incorporating surgery, combination chemotherapy, and radiation therapy, the outcome for children with extensive, recurrent or metastatic disease remains poor. RMS in the head and neck region can be misdiagnosed as an infective or inflammatory swelling, thereby delaying the treatment. Here, we report a case of oral RMS in a 10-year-old child and highlight the need to include sinister pathologies like RMS in the differential diagnosis when dealing with cheek swellings in the paediatric age group.